Anaesthetic death: who pays?. Issue 5 (10th May 2013) - Fawcett, Anne
Abstract : THIS series gives readers the opportunity to consider and contribute to discussion of some of the ethical dilemmas that can arise in veterinary practice. Each month, a case scenario is presented, followed by discussion of some of the issues involved. In addition, a possible way forward is suggested; however, there is rarely a cut‐and‐dried answer in such cases, and readers may wish to suggest an alternative approach. This month's dilemma, 'Anaesthetic death: who pays?', was presented and discussed by Anne Fawcett. Readers with comments to contribute are invited to send them as soon as possible, so that they can be considered for publication in the next issue. Discussion of the dilemma 'Is flirting with clients taboo?', which was published in the April issue of In Practice, appears on page 287. The series is being coordinated by Siobhan Mullan, of the University of Bristol. It is hoped it will provide a framework that will help practices find solutions when facing similar dilemmas.